Fixed combination of topical brimonidine 0.2% and timolol 0.5% for glaucoma and uncontrolled intraocular pressure - Anne J Lee (Dove Medical Press, 2008)
Anne J Lee1, Peter McCluskey1,21Department of Ophthalmology, Liverpool Hospital, Liverpool, NSW, Australia; 2Faculty of Medicine, University of New South Wales, Randwick, NSW, AustraliaAbstract: Lowering IOP is the most readily modifiable risk factor to delay the development and progression of glaucoma (POAG). The fixed combination of brimonidine tartrate 0.2% and timolol maleate 0.5% (FCBT) combines a highly selective α2-adrenergic agonist (brimonidine) with a non-selective β-blocker (timolol). FCBT reduces aqueous production and enhances uveoscleral outflow. Concomitant brimonidine and timolol have additive effects on reducing intraocular pressure (IOP). Multi-center randomized control trials have documented superiority of FCBT twice daily on IOP control compared with monotherapy with the individual components, and equal efficacy compared with concomitant therapy. IOP reduction with FCBT versus fixed combination dorzolamide 2% and timolol 0.5% (FCDT) was similar in a small study. Other studies (n > 293) evaluating concomitant brimonidine and timolol have shown that it is not inferior to FCDT. However, concomitant brimonidine and timolol administered twice daily was significantly less efficacious in IOP reduction than fixed combination latanoprost 0.005% and timolol 0.5% (FCLT). There are no published studies comparing FCBT with FCLT. The side effect profile for FCBT reflects that of its individual components. FCBT was generally well tolerated, with less ocular side effects than brimondine alone, but more than timolol alone. Documented systemic effects were few, although this could be confounded by selection bias. FCBT is a safe and effective IOP lowering agent for POAG and ocular hypertension.Keywords: brimonidine, timolol, combigan, glaucoma, combination, ocular hypertension